2016
DOI: 10.1111/sjop.12313
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effect of Facebook: Priming with online social networking may boost felt relatedness that buffers against physical pain

Abstract: Social networking sites (SNSs) are extremely popular for providing users with a convenient platform for acquiring social connections and thereby feeling relatedness. Plenty of literature has shown that mental representations of social support can reduce the perception of physical pain. The current study tested whether thinking about SNS would interfere with users' perceptions of experimentally induced pain. Ninety-six undergraduate Facebook users were recruited to participate in a priming-based experiment. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
(53 reference statements)
3
7
0
Order By: Relevance
“…We showed that priming with SNS was associated with an increased desirability of offline solitary activity (Experiment 1), a higher preference for working alone (Experiment 1), a decreased desirability of offline socializing (Experiment 2), and a lower desirability of offline pleasurable experiences (Experiment 2). Our findings complement the priming literature showing that mere exposure to SNS primes may influence perceptions and behaviors (e.g., priming with affiliation motivation via affiliation arousal or social exclusion can prompt the idea of SNSs, Lee & Chiou, ; priming with SNSs can neutralize perceived distress related to social exclusion and thinking about thinking about being unable to access SNSs can increase experienced distress of social exclusion, Chiou et al ., ; exposure to SNS primes can lower perceptions of physical pain, Ho et al ., ). Moving beyond the prime‐to‐behavior effects (Wheeler et al ., ), our research suggests that reminders of perceived access to social relatedness in cyberspace (i.e., online social networking) may be sufficient to impede social engagement in offline space.…”
Section: General Discussion and Conclusionmentioning
confidence: 97%
See 3 more Smart Citations
“…We showed that priming with SNS was associated with an increased desirability of offline solitary activity (Experiment 1), a higher preference for working alone (Experiment 1), a decreased desirability of offline socializing (Experiment 2), and a lower desirability of offline pleasurable experiences (Experiment 2). Our findings complement the priming literature showing that mere exposure to SNS primes may influence perceptions and behaviors (e.g., priming with affiliation motivation via affiliation arousal or social exclusion can prompt the idea of SNSs, Lee & Chiou, ; priming with SNSs can neutralize perceived distress related to social exclusion and thinking about thinking about being unable to access SNSs can increase experienced distress of social exclusion, Chiou et al ., ; exposure to SNS primes can lower perceptions of physical pain, Ho et al ., ). Moving beyond the prime‐to‐behavior effects (Wheeler et al ., ), our research suggests that reminders of perceived access to social relatedness in cyberspace (i.e., online social networking) may be sufficient to impede social engagement in offline space.…”
Section: General Discussion and Conclusionmentioning
confidence: 97%
“…For instance, priming individuals with the concept of money appears to increase their feelings of self‐sufficiency, leading to a stronger preference for playing and working alone (Vohs, Mead & Goode, , ). A recent study demonstrated that participants exposed to SNS primes reported less experimentally induced pain than did both the neutral‐prime and no‐prime groups (Ho et al ., ). In a similar vein, we contend that reminders of SNSs may lead to a belief that social connections are potentially obtainable.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The interface of the application can form the social interface in such a way that the mere presence of social cues gives rise to a feeling of being connected with others (Biocca et al, 2003;Metzger et al, 2010). According to one of the studies in the health domain by Ho et al (2016), the need for relatedness increased by simply priming users with the social media logo. A study by Zhang et al (2015) showed an increase in workout enrollment by users who saw the peers' profiles and progress.…”
Section: Need For Relatednessmentioning
confidence: 99%